STUDI IN VITRO EKSTRAK DAUN TEMBAKAU (Nicotiana tabacum) DAN DAUN BINAHONG HIJAU (Anredera cordifolia steenis) SEBAGAI INSEKTISIDA ALAMI UNTUK MYIASIS PADA RUMINANSIA - Teguh Dwi Putra; Nur Taufiq; Hamzah Nata Siswara; Lia Nur Aini; Khoirul Huda (Wahana Peternakan, 2022)
The purpose of this study was to determine the effectiveness of the combination of tobacco leaf extract (Nicotiana tabacum) and green binahong leaf (Anredera cordifolia steenis) against myiasis. The study used the in vitro method for testing, while the leaf extract was obtained using the immersion method. This research was conducted using a completely randomized design (CRD) with a one-way pattern (One Way ANNOVA) with 6 treatments and 4 replications. The test uses fresh beef samples that have been rotten for 6 days at room temperature. The fresh weight of each meat sample was 100 grams. The treatments were P0 (control: only water), P1 (100% tobacco), P2 (100% green binahong), P3 (50% tobacco: 50% green binahong), P4 (70% tobacco: 30 green binahong) and P5 (30% tobacco: 70% green binahong). The results observed in the study included the time (seconds) required for larvae to come out of the meat after spraying on each treatment, the death of myiasis larvae at 5, 10, 15, and 25 minutes. The results showed that treatment P4 got the best results. compared with other treatments with a significant difference at the level of p <0.05. Key words: Tobacco leaves, Binahong leaves, Myiasis, Animal health.